Thermally conductive double-sided adhesive tape and method for producing same

CN119823662APending Publication Date: 2025-04-15SHIN ETSU CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510105192.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-04-24
Filing Date
2020-04-20
Publication Date
2025-04-15

Smart Images

  • Figure BDA0005255239060000031
    Figure BDA0005255239060000031
  • Figure BDA0005255239060000101
    Figure BDA0005255239060000101
  • Figure BDA0005255239060000121
    Figure BDA0005255239060000121
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a thermally conductive composite which is in the form of a sheet, has good handling properties, excellent strength and insulating properties, can be easily fixed to an element or a heat-dissipating member, and has excellent bonding strength with the heat-dissipating member; and a method for producing the thermally conductive composite. A thermally conductive composite has: a first thermally conductive adhesive layer; a reinforcing layer (A) laminated on one surface of the first thermally conductive adhesive layer; and a second thermally conductive adhesive layer laminated on the surface of the reinforcement layer (A) on the opposite side from the one surface, the thermally conductive composite being characterized in that the first thermally conductive adhesive layer and the second thermally conductive adhesive layer independently contain a silicone composition containing components (a) to (e).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention is a divisional application of the invention patent application with application number 202080030132.2 filed on April 20, 2020 and invention name “Thermal Conductive Composite and Method for Manufacturing the Same”. Technical Field

[0002] The present invention relates to a heat conductive hardened material that can be inserted and mounted between a heat boundary surface of a heat generating element and a heat sink or a circuit board, in particular, for cooling the heat generating element, and a method for manufacturing the same. Background Art

[0003] Semiconductors such as transistors or diodes used in electronic devices such as converters or power supplies, and light emitting diode (LED) components that serve as light sources for lighting or displays, generate a large amount of heat as they become more high-performance, faster, smaller, and more integrated. The temperature rise of the equipment caused by the heat can cause malfunction or damage. Therefore, a large number of heat dissipation methods for suppressing the temperature rise of semiconductors in operation and heat dissipation components used in these methods have been proposed.

[0004] In the past, in electronic devices, in order to suppress the temperature rise of semiconductors in operation, the heat generated by the semiconductor was transferred to a cooling member such as a radiator or a frame using a metal plate with high thermal conductivity such as aluminum or copper via a thermally conductive material, and the heat was released to the outside through the temperature difference with the environment. As a thermally conductive material, an insulating thermally conductive sheet is often used. In addition, screws or clips are used to fix the cooling member and the semiconductor. In addition, the thermally conductive sheet interposed between them is also fixed by pressing with screws or clips. However, the fixing method using screws or clips must go through the steps of preparing screws or clips, opening holes for screw fixing in the frame, semiconductor element, substrate, etc., and fixing them. The number of parts and steps will increase, which is very disadvantageous in terms of manufacturing efficiency. In addition, due to parts such as screws or clips, the miniaturization or thinning of the electronic device itself is hindered, which is also very disadvantageous in terms of product design.

[0005] Therefore, a method of fixing the frame and the semiconductor element by imparting adhesiveness to the thermally conductive sheet interposed between the cooling member and the semiconductor is considered. Specifically, there is a method of applying an adhesive on both sides of the thermally conductive sheet to make a thermally conductive sheet with an adhesive, but since the adhesive itself has no thermal conductivity, the heat transfer of the thermally conductive sheet with an adhesive is significantly deteriorated. Therefore, a thermally conductive adhesive tape is known in which an adhesive material is filled with a thermally conductive filler, such as described in Patent Document 1, Patent Document 2, and Patent Document 3. In addition, in Patent Document 4, a thermally conductive silicone adhesive tape using silicone as a polymer is known due to the heat resistance, cold resistance, and durability of silicone.

[0006] [Prior art literature]

[0007] [Patent Document]

[0008] Patent Document 1: Japanese Patent Application Publication No. 2014-34652

[0009] Patent Document 2: Japanese Patent Application Publication No. 2014-62220

[0010] Patent Document 3: Japanese Patent Application Publication No. 2002-121529

[0011] Patent Document 4: Japanese Patent No. 5283346 Summary of the invention

[0012] [Problems to be solved by the invention]

[0013] However, compared with general adhesive materials, existing adhesive tapes lack adhesive strength and have problems in screw-free. In addition, in the case of a single-layer adhesive tape, there is room for improvement in workability, insulation, and strength. In addition, since it is a heat-curing adhesive that is not in sheet form, the operation steps during coating become complicated, so compared with adhesive (adhesive) sheets, the workability is poor and there is also a risk of mixing into gaps, so there are also problems in ensuring insulation.

[0014] Therefore, an object of the present invention is to provide a thermally conductive composite tape which is easy to handle due to its sheet shape, has excellent strength and insulation, can be easily fixed to an element or a heat dissipating member, and has excellent bonding strength with the heat dissipating member.

[0015] [Technical means to solve the problem]

[0016] The inventors of the present invention have conducted extensive research to achieve the above-mentioned purpose, and have found that: a thermally conductive composite tape is characterized in that a thermally conductive adhesive layer containing a silicone resin and a thermally conductive filler and having adhesion is used as an outer layer and is laminated on both sides of a reinforcing layer, and by specifically specifying the composition of the silicone resin contained in the silicone composition providing the thermally conductive adhesive layer and the formulation amount of the thermally conductive filler, a bonding layer with strength and insulation, good handling properties, and good bonding strength with a heat-generating element is provided, thereby completing the present invention.

[0017] In addition, if an addition reaction type adhesive composition is used, there is a concern that the adhesive layer will harden over time even at room temperature after being manufactured and before being laminated with the reinforcing layer, and the manufacturing conditions of the composite tape will be unstable. Furthermore, there is a concern that the hardness of the adhesive layer will increase at room temperature after the composite tape is manufactured, and there is a concern that the storage stability will be poor. Therefore, the object of the present invention is to solve these problems by making a peroxide-curable silicone composition.

[0018] Therefore, the present invention provides a thermally conductive composite, comprising: a first thermally conductive adhesive layer; a reinforcing layer (A) laminated on one surface of the first thermally conductive adhesive layer; and a second thermally conductive adhesive layer laminated on the surface of the reinforcing layer (A) opposite to the one surface, wherein the thermally conductive composite is characterized in that:

[0019] The first thermally conductive adhesive layer and the second thermally conductive adhesive layer independently include a silicone composition containing the following components (a) to (e).

[0020] (a) Straight-chain or branched organopolysiloxane: 100 parts by mass

[0021] (b) Thermally conductive filler: 1,000 to 3,000 parts by mass

[0022] (c) Silicone resin: 100 to 500 parts by mass

[0023] (d) organohydrogenpolysiloxane: 1 to 10 parts by mass, and

[0024] (e) Organic peroxide: 0.5 to 5 parts by mass.

[0025] The present invention also provides the thermally conductive composite, wherein the silicone composition further contains 1 to 20 parts by mass of (f) at least one selected from the following components (f-1) and (f-2).

[0026] (f-1) Alkoxysilane compound represented by the following general formula (1)

[0027] R 2a R 3 b Si(OR 4 ) 4-a-b (1)

[0028] (Where R 2 are independently an alkyl group having 6 to 15 carbon atoms, R 3 are independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, R 4 are independently an alkyl group having 1 to 6 carbon atoms, a is an integer of 1 to 3, b is an integer of 0 to 2, wherein a+b is an integer of 1 to 3)

[0029] (f-2) Dimethyl polysiloxane represented by the following general formula (2)

[0030] [Chemistry 1]

[0031]

[0032] (Where R 5 are independently an alkyl group having 1 to 6 carbon atoms, and c is an integer of 5 to 100)

[0033] [Effects of the Invention]

[0034] The thermally conductive composite tape of the present invention has good strength, handling properties, and insulation properties, and can be easily transferred to a heat-generating element or a heat-dissipating member. In addition, the thermally conductive adhesive layer imparts preferred thermal conductivity between the heat-generating element and the heat-dissipating member, and exhibits good bonding strength, thereby enabling fixation between the members. The thermally conductive composite tape of the present invention is very effective as a heat-conductive member that exists between the heat-generating element and the heat-dissipating member and transfers the heat generated by the heat-generating element to the heat-dissipating member and fixes the heat-generating member. DETAILED DESCRIPTION

[0035] [(A) Enhancement layer]

[0036] The reinforcing layer in the composite sheet of the present invention is preferably glass cloth or a synthetic resin film layer which is excellent in heat resistance and electrical insulation and is flexible and has high mechanical strength, and can be appropriately selected from known substrates for use.

[0037] The glass cloth may have a thickness of 10 μm or more and 50 μm or less, and preferably has a weight of 45 g / m 2 More preferably, it is 20 μm or more and 40 μm or less, and its weight is preferably 30 g / m 2Below. The thermal conductivity of glass cloth is relatively low, so if thermal conductivity is taken into consideration, it is preferably thin. However, if it is too thin, the strength will decrease and it will be easy to break, or it will lack formability, so the thickness within the above range is preferred. The glass cloth can also be pre-filled with a silicone composition that forms a thermally conductive adhesive layer described later. Alternatively, the thermally conductive adhesive layer can be directly attached without pre-filling. In the latter case, the mesh of the cloth is easily filled with the thermally conductive adhesive layer by performing hot pressing, so it is preferred.

[0038] The synthetic resin film layer usually has a thickness of 2 μm to 30 μm, preferably in the range of 5 μm to 20 μm. If the synthetic resin film layer is too thick, the thermal conductivity of the composite sheet of the present invention will be hindered. On the contrary, if it is too thin, the strength that should be exerted as a reinforcing layer is insufficient, and the withstand voltage characteristics are deteriorated, and there is a situation where the electrical insulation performance becomes insufficient. Furthermore, the synthetic resin film layer is preferably a film layer without holes that reduce the withstand voltage characteristics.

[0039] Examples of the synthetic resin include aromatic polyimide, polyamide, polyamide-imide, polyesters such as polyethylene naphthalate, and fluorine-based polymers such as polytetrafluoroethylene (PTFE) and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers. When the fluorine-based polymer is used as the synthetic resin, it is preferred to perform chemical etching on the surface of the film to be used using a metal Na / naphthalene-based treatment solution from the viewpoint of improving adhesion.

[0040] In order to prevent the mechanical strength from being reduced due to thermal deformation, the synthetic resin film is particularly preferably a heat-resistant film having a melting point of 200° C. or more, preferably 250° C. or more. As a heat-resistant synthetic resin film having a melting point of 250° C. or more, for example, Kapton (registered trademark) MT (trade name, manufactured by Toray Dupont Co., Ltd.), which is an aromatic polyimide film, can be cited.

[0041] [(B) Thermally conductive adhesive layer]

[0042] The thermally conductive silicone composite sheet of the present invention has a first thermally conductive adhesive layer and a second thermally conductive adhesive layer on both sides of the reinforcing layer (A). The compositions of the first thermally conductive adhesive layer and the second thermally conductive adhesive layer may be the same or different. The thermally conductive adhesive layer is obtained by drying a silicone composition containing the following components (a) to (e) to form a thin layer.

[0043] (a) Organopolysiloxane: 100 parts by mass

[0044] (b) Thermally conductive filler: 1,000 to 3,000 parts by mass

[0045] (c) Silicone resin: 100 to 500 parts by mass

[0046] (d) Organohydrogenpolysiloxane: 1 to 10 parts by mass

[0047] (e) Organic peroxide: 0.5 to 5 parts by mass

[0048] Hereinafter, each component will be described in detail.

[0049] [(a) Organopolysiloxane]

[0050] The component (a) is a linear or branched organopolysiloxane, and is preferably represented by the following average composition formula (3).

[0051] R 1 n SiO (4-n) / 2 (3)

[0052] (Where R 1 are independently unsubstituted or substituted monovalent hydrocarbon groups, and n is a positive number ranging from 1.98 to 2.02)

[0053] In the formula, R 1 Each of them is independently an unsubstituted or substituted monovalent hydrocarbon group, preferably an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, more preferably an unsubstituted or substituted monovalent hydrocarbon group having 1 to 8 carbon atoms. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, and butyl groups, cycloalkyl groups such as cyclohexyl groups, alkenyl groups such as vinyl, allyl, butenyl, and hexenyl groups, aryl groups such as phenyl and tolyl groups, and chloromethyl, trifluoropropyl, and cyanoethyl groups in which a part or all of the hydrogen atoms bonded to the carbon atoms of these groups are substituted with halogen atoms, cyano groups, and the like. Methyl, vinyl, phenyl, and trifluoropropyl groups are more preferred, and R 1 50 mol % or more, particularly 80 mol % or more, of the groups are methyl groups.

[0054] In addition, it is preferred that 2 or more, more preferably 2 to 20, and more preferably 2 to 10 alkenyl groups such as vinyl, allyl, butenyl, and hexenyl may be present in the molecule.

[0055] (a) The organopolysiloxane is preferably linear, and may have several branches within a range that does not impair the rubber strength as a thermally conductive adhesive layer. In addition, it may be a mixture of two or more organopolysiloxanes having different molecular structures or polymerization degrees. Furthermore, the organopolysiloxane preferably has an average polymerization degree of 100 to 20,000, especially 3,000 to 10,000. The average polymerization degree can be obtained as a number average polymerization degree of polystyrene conversion obtained by gel permeation chromatography (GPC).

[0056] [(b) Thermally conductive filler]

[0057] (b) The thermally conductive filler may be a known filler contained in the thermally conductive composition, preferably one or more selected from the group consisting of metals, metal oxides, and metal nitrides. As long as it is a known thermally conductive filler such as non-magnetic copper, metals such as aluminum, aluminum oxide, silicon dioxide, magnesium oxide, ferric oxide (bengala), beryllium oxide, titanium dioxide, and zirconium oxide, metal nitrides such as aluminum nitride, silicon nitride, and boron nitride, artificial diamond or silicon carbide. The thermally conductive filler may have an average particle size of 0.1 μm to 50 μm, preferably 0.5 μm to 40 μm, and more preferably 1 μm to 30 μm. The thermally conductive filler may be used alone or in combination. In addition, two or more particles with different average particle sizes may also be used. Furthermore, in the present invention, the average particle size is a volume average particle size, which is a measured value obtained using a Microtrac particle size distribution measuring device MT3300EX (Nikkiso Co., Ltd.).

[0058] The amount of the thermally conductive filler is 1,000 to 3,000 parts by mass, preferably 1,500 to 2,500 parts by mass, relative to 100 parts by mass of component (a). If the amount of the thermally conductive filler is too large, the adhesiveness of the tape is impaired and workability is reduced. If it is too small, the desired thermal conductivity cannot be obtained.

[0059] [(c) Silicone resin]

[0060] (c) The silicone resin is added to impart adhesiveness to the cured product of the silicone composition (ie, the thermally conductive adhesive layer).

[0061] (c) The composition is R3SiO 1 / 2 Unit (M unit) and SiO 4 / 2 The copolymer of the present invention is characterized in that the ratio (molar ratio) of the M unit to the Q unit is M / Q = 0.5 to 3.0, preferably 0.7 to 1.4, and more preferably 0.9 to 1.2. When M / Q is less than 0.5 or exceeds 3.0, the desired adhesive force cannot be obtained.

[0062] In the M unit, R is independently an unsubstituted or substituted monovalent hydrocarbon group having no aliphatic unsaturated bond, and may be an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms. For example, alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, decyl and dodecyl; cycloalkyl groups such as cyclopentyl, cyclohexyl and cycloheptyl; aryl groups such as phenyl, tolyl, xylyl, naphthyl and biphenyl; aralkyl groups such as benzyl, phenylethyl, phenylpropyl and methylbenzyl; and groups in which a part or all of hydrogen atoms bonded to carbon atoms of these groups are substituted with halogen atoms such as fluorine, chlorine and bromine, cyano and the like, for example, chloromethyl, 2-bromoethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, chlorophenyl, fluorophenyl, cyanoethyl and 3,3,4,4,5,5,6,6,6-nonafluorohexyl. Among them, unsubstituted or substituted alkyl groups having 1 to 3 carbon atoms and unsubstituted or substituted phenyl groups such as phenyl, chlorophenyl, and fluorophenyl are preferred, and methyl, ethyl, propyl, chloromethyl, bromoethyl, 3,3,3-trifluoropropyl, and cyanoethyl are more preferred. 1 The same or different, ideally the same as R 1 In addition, R and R 1 Similarly, unless special properties such as solvent resistance are required, all methyl groups are most preferably used for reasons such as cost, availability, chemical stability, and environmental load. The viscosity of a 60% toluene solution of the silicone resin at 25° C. may be 3 mPa·s to 20 mPa·s, preferably 6 mPa·s to 12 mPa·s. The viscosity can be measured using a rotational viscometer.

[0063] Relative to 100 parts by mass of component (a), the amount of component (c) is 100 to 500 parts by mass, preferably 150 to 400 parts by mass, and more preferably 200 to 350 parts by mass. When the amount of component (c) added is less than the lower limit, the thermally conductive composite tape cannot obtain the desired bonding strength. In addition, when the upper limit is exceeded, the adhesiveness of the tape becomes very strong, and the workability when the tape body is peeled off from the substrate is reduced. Furthermore, component (c) itself is a solid or viscous liquid at room temperature, and can also be used in a state dissolved in a solvent. In the case, the amount added to the composition can be adjusted in such a way that the resin component after removing the solvent component satisfies the range.

[0064] [(d) Organohydrogenpolysiloxane]

[0065] Component (d) is an organohydrogenpolysiloxane having at least two hydrogen atoms (SiH groups, i.e., hydrosilyl groups) bonded to silicon atoms in one molecule, and functions to exhibit good wettability at the interface with the adherend and to improve the bonding strength. The organohydrogenpolysiloxane can be any known compound, and can be a compound that does not substantially contain a hydroxyl group (i.e., silanol group) bonded to a silicon atom in the molecule. One organohydrogenpolysiloxane can be used alone or two or more can be used in combination.

[0066] The organohydrogenpolysiloxane can be represented by the following average composition formula (4).

[0067] R 8 a H b SiO (4-a-b) / 2 (4)

[0068] In the formula (4), R 8 Each of them is independently an unsubstituted or substituted monovalent hydrocarbon group having preferably 1 to 10 carbon atoms, more preferably 1 to 8 carbon atoms. Among them, there is no aliphatic unsaturated bond such as alkenyl. As unsubstituted or substituted monovalent hydrocarbon groups, for example, alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, octyl, nonyl, and decyl, aryl groups such as phenyl, tolyl, xylyl, and naphthyl, aralkyl groups such as benzyl, phenylethyl, and phenylpropyl, etc. can be listed. Among them, alkyl groups or aryl groups are preferred, and methyl groups are more preferred. In addition, a is a positive number of 0.7 to 2.1, b is a positive number of 0.001 to 1.0, and a+b is a number satisfying the range of 0.8 to 3.0. Preferably, a is a positive number of 1.0 to 2.0, b is a positive number of 0.01 to 1.0, and a+b is a number satisfying the range of 1.5 to 2.5.

[0069] The organohydrogenpolysiloxane has at least two (usually 2 to 200), preferably 3 or more (for example, 3 to 100), and more preferably 4 to 50 SiH groups in one molecule. The SiH group may be located at any position at the end of the molecular chain or in the middle of the molecular chain, and may also be located at these two positions. The molecular structure of the organohydrogenpolysiloxane may be any of a linear, cyclic, branched, and three-dimensional network structure. The number of silicon atoms (or degree of polymerization) in one molecule is usually 2 to 300, preferably 3 to 150, and more preferably 4 to 100. Furthermore, the degree of polymerization can be obtained, for example, as the number average degree of polymerization (number average molecular weight) converted to polystyrene in GPC (gel permeation chromatography) analysis using toluene as the developing solvent.

[0070] Examples of the organohydrogenpolysiloxane include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(hydrogendimethylsiloxy)methylsilane, tris(hydrogendimethylsiloxy)phenylsilane, methylhydrogencyclopolysiloxane, methylhydrogensiloxane-dimethylsiloxane cyclic copolymer, methylhydrogenpolysiloxane having both ends of the molecular chain capped with trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymer having both ends of the molecular chain capped with trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane-methylphenylsiloxane copolymer having both ends of the molecular chain capped with trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane-diphenylsiloxane copolymer having both ends of the molecular chain capped with trimethylsiloxy groups, and the like. Methylhydrogen polysiloxane having both ends of the molecular chain terminated by dimethylhydrogen siloxy groups, dimethyl polysiloxane having both ends of the molecular chain terminated by dimethylhydrogen siloxy groups, dimethyl siloxane-methylhydrogen siloxane copolymer having both ends of the molecular chain terminated by dimethylhydrogen siloxy groups, dimethyl siloxane-methylphenyl siloxane copolymer having both ends of the molecular chain terminated by dimethylhydrogen siloxy groups, dimethyl siloxane-diphenyl siloxane copolymer having both ends of the molecular chain terminated by dimethylhydrogen siloxy groups, methyl phenyl polysiloxane having both ends of the molecular chain terminated by dimethylhydrogen siloxy groups, and diphenyl polysiloxane having both ends of the molecular chain terminated by dimethylhydrogen siloxy groups, compounds in which part or all of the methyl groups in the above compounds are substituted by other alkyl groups such as ethyl groups and propyl groups, and compounds containing the formula: R 2 3SiO 1 / 2 (R in the formula 2 is a monovalent hydrocarbon group other than an alkenyl group, and is 1 The siloxane unit represented by the same group) and the formula: R 2 2HSiO 1 / 2 The siloxane unit and formula represented: SiO 4 / 2 An organosiloxane copolymer of a siloxane unit represented by 2 2HSiO 1 / 2 The siloxane unit represented by the formula: SiO 4 / 2 An organosiloxane copolymer of a siloxane unit represented by 2 HSiO 2 / 2 The siloxane unit represented by the formula: R 2 SiO 3 / 2 The siloxane unit or formula represented is: HSiO 3 / 2 These organohydrogenpolysiloxanes may be used in combination of two or more.

[0071] The amount of component (d) is 1 to 10 parts by mass, preferably 2 to 9 parts by mass, relative to 100 parts by mass of component (a). If the amount of component (d) is less than the lower limit, the adhesion to the adherend is reduced. In addition, if the upper limit is exceeded, the adhesive layer becomes fragile, so the adhesive strength is reduced.

[0072] [(e) Organic peroxides]

[0073] (e) component is an organic peroxide that decomposes under specific conditions to produce ionized free radicals, and functions to promote the curing of the thermally conductive adhesive layer at high temperatures and improve the adhesive strength. The organic peroxide may be a known compound, and is not particularly limited. It may be used alone or in combination of two or more. For example, peroxyketals such as 1,1-di(tert-butylperoxy)cyclohexane and 2,2-di(4,4-di-(tert-butylperoxy)cyclohexyl)propane, hydroperoxides such as p-menthane hydroperoxide and diisopropylbenzene hydroperoxide, dialkyl peroxides such as diisopropyl peroxide and tert-butylisopropyl peroxide, diacyl peroxides such as dibenzoyl peroxide and disuccinic acid peroxide, peroxyesters such as tert-butyl peroxyacetate and tert-butyl peroxybenzoate, and peroxydicarbonates such as diisopropyl peroxydicarbonate. In particular, from the viewpoint of handling or storage properties, it is preferred to use peroxyketals, hydroperoxides, dialkyl peroxides, and peroxyesters having relatively high decomposition temperatures. In addition, these organic peroxides may also be used in the form of dilutions of any organic solvent or hydrocarbon, liquid paraffin, or an inert solid.

[0074] Relative to 100 parts by mass of component (a), the amount of component (e) is 0.5 to 5 parts by mass, preferably 1 to 3 parts by mass. If the amount of component (e) is less than the lower limit, the thermal conductive adhesive layer is not fully hardened during thermal compression with the heating element, and the bonding strength is reduced. In addition, if the upper limit is exceeded, the strength of the bonding layer is reduced due to the large amount of decomposition residues produced during thermal compression, and the bonding strength is also reduced.

[0075] [(f) Surface treatment agent]

[0076] The silicone composition preferably further comprises (f) a surface treatment agent. The component (f) is used to uniformly disperse the thermally conductive filler (b) in the matrix comprising the organopolysiloxane (a) when preparing the composition. The component (f) is at least one selected from the group consisting of the alkoxysilane compound represented by the component (f-1) and the dimethylpolysiloxane containing a trialkoxy group at one end of the molecular chain represented by the component (f-2). The components (f-1) and (f-2) may be either one or both.

[0077] (f-1) Alkoxysilane compound represented by the following general formula (1)

[0078] R 2 a R 3 b Si(OR 4 ) 4-a-b (1)

[0079] (Where R 2 are independently an alkyl group having 6 to 15 carbon atoms, R 3 are independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, R 4 are independently an alkyl group having 1 to 6 carbon atoms, a is an integer of 1 to 3, b is an integer of 0 to 2, wherein a+b is an integer of 1 to 3)

[0080] (f-2) Dimethyl polysiloxane represented by the following general formula (2)

[0081] [Chemistry 2]

[0082]

[0083] (Where R 5 are independently an alkyl group having 1 to 6 carbon atoms, and c is an integer of 5 to 100)

[0084] In the general formula (1), R 2 The alkyl group represented by may be, for example, hexyl, octyl, nonyl, decyl, dodecyl, and tetradecyl. 2 When the number of carbon atoms of the alkyl group represented is within the range of 6 to 15, the wettability of the component (c) is sufficiently improved, the handling property is good, and the low-temperature characteristics of the composition are good.

[0085] R 3It is an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, preferably a monovalent hydrocarbon group having 1 to 8 carbon atoms, particularly preferably a monovalent hydrocarbon group having 1 to 6 carbon atoms. Examples thereof include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl; aryl groups such as phenyl, tolyl, xylyl, naphthyl, and biphenyl; aralkyl groups such as benzyl, phenylethyl, phenylpropyl, and methylbenzyl; and groups in which a part or all of hydrogen atoms bonded to carbon atoms of these groups are substituted with halogen atoms such as fluorine, chlorine, and bromine, or cyano, such as chloromethyl, 2-bromoethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, chlorophenyl, fluorophenyl, cyanoethyl, and 3,3,4,4,5,5,6,6,6-nonafluorohexyl. Preferred examples include unsubstituted or substituted alkyl groups having 1 to 3 carbon atoms such as methyl, ethyl, propyl, chloromethyl, bromoethyl, 3,3,3-trifluoropropyl and cyanoethyl, and unsubstituted or substituted phenyl groups such as phenyl, chlorophenyl and fluorophenyl.

[0086] R 4 and R 5 Each of them is independently an alkyl group having 1 to 6 carbon atoms, preferably an alkyl group having 1 to 4 carbon atoms. Examples thereof include methyl, ethyl, propyl, and butyl groups. A methyl group is more preferred.

[0087] The amount of component (f) is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, and even more preferably 3 to 10 parts by mass relative to 100 parts by mass of component (a). When the amount of component (f) added is less than 1 part by mass, component (b) cannot be filled into component (a), and when it exceeds 20 parts by mass, the bonding strength of the composite tape is reduced.

[0088] In addition to the components (a) to (f), the silicone composition may also contain a surface treatment agent for a thermally conductive filler, a pigment and / or dye for coloring, a flame retardant imparting agent, and various additives for improving other functions within a range that does not impair the purpose of the present invention.

[0089] The silicone composition is prepared by uniformly mixing the components (a) to (e) and any component (f), as well as other components. The mixing method can be in accordance with the existing known method. Preferably, after mixing the components (a), (b) and (c), and any component (f), the components (d) and (e) are mixed. The thermally conductive adhesive layer of the present invention can be obtained by applying the silicone composition in the form of a thin film strip on both sides of the substrate (i.e., the reinforcing layer (A)), forming it and drying it. The drying conditions are 5 minutes to 15 minutes at 60°C to 100°C, preferably 5 minutes to 10 minutes at 70°C to 90°C. When the drying conditions are outside the range, the thermal conductivity is reduced due to the residual solvent, or the composition is cured, so when it is attached and installed on the heating element, the transferability is reduced. The thermally conductive adhesive layer is a silicone composition in an uncured state. When it is installed between the heat-dissipating component and the heat-generating component, it can be cured by using the heat generated by the heating element.

[0090] The thickness of the thermally conductive adhesive layer is preferably 50 μm to 300 μm, more preferably 75 μm to 200 μm. If the thickness of the adhesive layer is less than 50 μm, the handling of the tape is poor and the adhesive force is reduced. On the other hand, if the thickness of the adhesive layer exceeds 300 μm, the desired thermal conductivity cannot be obtained. In addition, during coating and forming, a solvent such as toluene or xylene may be added to adjust the viscosity.

[0091] The thermally conductive composite of the present invention may further have a substrate surface-treated with a release agent as a separator film (hereinafter sometimes referred to as a release-treated film). That is, the release-treated surface of the substrate may be laminated on the surface of the thermally conductive adhesive layer that is not bonded to the reinforcing layer (A). The step of laminating the release-treated film on the thermally conductive adhesive layer may be performed after laminating the thermally conductive adhesive layer on both sides of the reinforcing layer, or the bonding surface of the thermally conductive adhesive layer pre-laminated on the release-treated surface of the release-treated film may be laminated on the reinforcing layer. By laminating the separator film on the bonding surface, transportation, cut-to-length and other processing can be easily performed. At this time, the peeling force of the separator film may be determined by changing the amount or type of the release agent and the material of the film.

[0092] As the separation membrane, it is preferred that the separation membrane is formed by subjecting at least one side of a paper or PET (polyethylene terephthalate) film to a demolding treatment using a fluorine-modified dimethyl silicone polymer. As the fluorine-modified dimethyl silicone polymer, there can be cited fluorine-modified dimethyl silicone oil (hereinafter referred to as fluorine-modified silicone) in which a fluorine substituent such as a perfluoroalkyl group or a perfluoropolyether group is bonded to the main chain. The perfluoropolyether group can be represented by the following formulas (5) to (7).

[0093] [Chemistry 3]

[0094]

[0095] (p is 1 to 5, q is 3 to 10)

[0096] As commercially available products of the fluorine-modified silicone, for example, X-70-201, X-70-258, and X-41-3035 manufactured by Shin-Etsu Chemical Co., Ltd. can be used. The forming method on the substrate can include coating the liquid material on the substrate using a rod coater, a knife coater, a notch wheel coater, a spin coater, etc., but is not limited to the described method.

[0097] [Method for producing thermally conductive composite]

[0098] Next, the method for producing the thermally conductive composite of the present invention is described in more detail. In the method for producing the thermally conductive composite of the present invention, the first thermally conductive adhesive layer and the second thermally conductive adhesive layer are respectively laminated on both sides of the reinforcing layer (A) as outer layers by room temperature compression or thermal compression. The lamination method is not particularly limited, and it can be appropriately performed according to the conventionally known method for producing a composite tape.

[0099] In the case of room temperature compression bonding, for example, the thermally conductive adhesive layer previously formed on the separation membrane can be transferred to both sides of the reinforcing layer (A). In the case of hot compression bonding, the pressing fixture is heated to 80°C to 120°C and the compression transfer is performed in the same manner. In addition to press compression bonding, roller compression bonding can also be used for compression bonding. In addition, the composition of the thermally conductive adhesive layer diluted with a solvent can also be applied to both sides of the reinforcing layer (A) and dried to produce a thermally conductive composite.

[0100] In addition, when glass cloth is used as a reinforcing layer, the glass cloth may be filled with the silicone composition in advance. When the silicone composition is applied to the glass cloth, a coating device such as a notch wheel coater, a knife coater, or a kiss coater equipped with a drying furnace, a heating furnace, and a winding device is used. After continuously applying the silicone composition to the glass cloth, the solvent is dried and / or evaporated, and then the silicone composition is heated and hardened at 100° C. to 180° C., preferably at about 120° C. to 150° C. for about 2 minutes to 10 minutes, thereby obtaining a glass cloth filled with the silicone composition.

[0101] Furthermore, unfilled glass cloth can also be used to transfer the thermally conductive adhesive layer formed on the separation membrane, thereby filling while laminating the thermally conductive adhesive layer. At this time, it is preferred to heat the pressing fixture to 80°C to 120°C for transfer. In addition to pressing and crimping, roller pressing and the like can also be used for crimping. When the transfer temperature is lower than 80°C, the thermally conductive adhesive layer is not well adhered to the glass cloth, and the mesh of the cloth is not buried, so a decrease in insulation or thermal conductivity is found. In addition, when it exceeds 120°C, the thermally conductive adhesive layer is also easily hardened, and a decrease in bonding force is easily generated when it is attached and installed on a heating element. The overall thickness of the thermally conductive composite can be 150μm to 500μm, preferably 200μm to 400μm.

[0102] Although the thermally conductive composite of the present invention is in the form of a thin strip or sheet, it can be easily arranged in the desired position and can exert excellent thermal conductivity. In addition, by having the separation membrane, after peeling off one of the separation membranes, it is attached to the heat-generating electronic component or the heat-releasing component, and then the remaining separation membrane is peeled off and attached to the cooling component, etc., thereby being interposed between the cooling component and the heat-generating electronic component or the heat-releasing component. Furthermore, by having a reinforcing layer (A), it becomes a double-sided adhesive tape with excellent insulation breakdown voltage or strength. Because there are thermally conductive adhesive layers on both sides, good adhesion can be achieved between the components by heating by the heating element or by heating and pressing during implementation, and it can be fixed. Regarding the heat treatment after attachment, it is carried out at 100°C to 170°C for 5 minutes to 60 minutes, preferably at 120°C to 150°C for 10 minutes to 30 minutes.

[0103] [Example]

[0104] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0105] The reinforcing layer (A) used in the following Examples and Comparative Examples, and the components (a) to (f) constituting the first thermally conductive adhesive layer and the second thermally conductive adhesive layer (B) are as follows.

[0106] [Enhancement layer (A)]

[0107] (X) Glass cloth: Unitika grey cloth H28F103 30μm, 28g / m 2

[0108] (Y) Polyimide: 30EN 7.5 μm manufactured by Kapton

[0109] [Thermal conductive adhesive layer (B)]

[0110] (a) Component: dimethylpolysiloxane raw rubber having an average degree of polymerization of 8,000 and dimethylvinyl groups at both ends

[0111] (b) Ingredients:

[0112] (b-1) Granular aluminum oxide having a volume average particle size of 1 μm

[0113] (b-2) Spherical aluminum oxide having a volume average particle size of 10 μm

[0114] (b-3) Granular boron nitride having a volume average particle size of 15 μm

[0115] (b-4) Spherical aluminum oxide having a volume average particle size of 30 μm

[0116] (c) Ingredients:

[0117] Toluene solution of MQ silicone resin (non-volatile content 60%, viscosity at 25°C 8 mPa·s, M / Q (molar ratio) = 0.95, all substituents bonded to the silicon atoms of the M unit are methyl groups)

[0118] Component (d): Cyclic organohydrogenpolysiloxane represented by the following formula

[0119] [Chemistry 4]

[0120]

[0121] Component (e): 1,1-di(tert-butylperoxy)cyclohexane represented by the following formula

[0122] [Chemistry 5]

[0123]

[0124] (f) Component: (f-2) dimethyl polysiloxane having an average degree of polymerization of 30 and having a trimethoxysilyl group at one end

[0125] The components (a), (b), (c), and (f) were added to a Shinagawa type multipurpose mixer according to the amounts listed in Table 1 or Table 2, and mixed for 60 minutes. Then, the components (d) and (e) were added according to the amounts listed in Table 1 or Table 2, and mixed uniformly to obtain a uniform thermally conductive silicone composition.

[0126] [Forming of thermally conductive adhesive layer]

[0127] Toluene was added in an appropriate amount to the obtained thermally conductive silicone composition. The toluene solution was applied to a fluorine-treated PET film (separation membrane), and the toluene was volatilized at 70° C. to form a thermally conductive adhesive layer having a thickness of 100 μm. The thickness of 100 μm was only the thickness of the thermally conductive adhesive layer and did not include the thickness of the separation membrane. The release agent used in the surface treatment of the fluorine-treated PET film (separation membrane) was X-41-3035 (manufactured by Shin-Etsu Chemical Co., Ltd.).

[0128] [Molding of thermally conductive composite (tape)]

[0129] A thermally conductive composite was formed by the following method using two laminated bodies of the separation membrane and the thermally conductive adhesive layer obtained as described above.

[0130] The composite using glass cloth (reinforcement layer (X)) was prepared by pressing a thermally conductive bonding layer formed on the separation membrane to both sides of the glass cloth at 100°C to form a thermally conductive composite (tape).

[0131] The composite using polyimide (reinforcement layer (Y)) is prepared by pressure-bonding a thermally conductive adhesive layer formed on the separation membrane to both sides of the polyimide at room temperature to form a thermally conductive composite (tape).

[0132] The thickness of the entire thermally conductive composite (tape) is as described in Tables 1 and 2. The size of the tape is 200 mm×300 mm.

[0133] In the examples and comparative examples, the compositions of the first thermally conductive adhesive layer and the second thermally conductive adhesive layer are the same and are as described in Table 1 or Table 2.

[0134] [Evaluation method]

[0135] (1) Transferability: When the adhesive layer of the thermally conductive composite is attached to the heat dissipating member (aluminum heat sink), whether the desired adhesion is obtained is evaluated.

[0136] After peeling off one side of the separation film and attaching the adhesive layer to the aluminum heat sink, peel off the separation film on the other side, and then evaluate whether the attached adhesive layer is fixed to the heat sink without deviation. In the table, the case where it can be fixed without deviation is recorded as ○, and the case where deviation occurs is recorded as ×.

[0137] (2) Thermal conductivity: After the separator films on both sides were peeled off, the thermally conductive composite was sandwiched between aluminum plates and pressed at room temperature / 20 psi / 1 hour, and then the thermal resistance was measured by the laser flash method. The thermal conductivity was calculated based on the relationship between thickness and thermal resistance.

[0138] (3) Shear strength against aluminum: A thermally conductive adhesive having a thickness listed in the table was sandwiched between 10 mm×10 mm square aluminum plates and pressure-bonded at 120° C. / 20 psi / 1 h, and then the peel shear stress at room temperature was measured.

[0139] (4) Dielectric breakdown voltage: The dielectric breakdown voltage of the thermally conductive composite after the separation films on both sides were peeled off was measured in accordance with Japanese Industrial Standards (JIS) K6249.

[0140] (5) Tensile strength: The tensile strength of the thermally conductive composite after the separators on both sides were peeled off was measured using an autograph in accordance with JIS K6249.

[0141] [Table 1]

[0142]

[0143] [Table 2]

[0144]

[0145] As shown in Table 2, if the amount of (d) organohydrogenpolysiloxane is too little, the wettability of the interface with the adherend is reduced, and the desired adhesion cannot be obtained (Comparative Example 1). If the amount of (d) organohydrogenpolysiloxane is too much, the strength of the composite tape is reduced, and the desired adhesion cannot be obtained (Comparative Example 2). If the amount of (c) silicone resin is small, the cohesive force of the composite tape is insufficient, and the transferability is difficult (Comparative Example 3). If the amount of (c) silicone resin is too much, it is difficult to peel off the composite tape from the separation membrane, and the transferability is difficult (Comparative Example 4). If the amount of (e) organic peroxide is small, the composite tape is not fully hardened when heated and pressed, and the adhesion strength is reduced (Comparative Example 5). If the amount of organic peroxide as (e) component is large, the strength of the composite tape is reduced due to the large amount of decomposition residues, and the desired adhesion cannot be obtained (Comparative Example 6). If the thermal conductive adhesive layer is set as a single layer without using a reinforcing layer, it is difficult in terms of mechanical strength or insulation (Comparative Example 7). On the other hand, when the amount of the thermally conductive filler (b) is too small, the thermal conductivity is insufficient (Comparative Example 8).

[0146] On the other hand, as shown in Table 1, the composite tape having the thermally conductive adhesive layer of the present invention is excellent in transferability and handling properties, and is also excellent in thermal conductivity and adhesive strength.

[0147] [Industrial Applicability]

[0148] The thermally conductive composite of the present invention has excellent handling properties, mechanical strength, insulation properties, and thermal conductivity, and can be easily transferred to components, and has good bonding strength to heat generating components. Therefore, it is suitable as a thermally conductive adhesive component (thermal conductive composite tape or sheet, etc.) that mediates between heat generating elements and heat dissipating components in semiconductor devices or electronic devices.

Claims

1. A thermally conductive double-sided adhesive tape, which is composed of a first adhesive layer and a second adhesive layer formed of a thermally conductive silicone composition laminated on both sides of a glass cloth, wherein the thermally conductive double-sided adhesive tape is characterized in that: The thermally conductive silicone composition comprises the following components (a) to (f), The glass cloth has a thickness of 10 μm or more and 50 μm or less, and a weight of 45 g / m 2 the following, The first bonding layer and the second bonding layer each have a thickness of 50 μm to 300 μm. (a) Straight-chain or branched organopolysiloxane: 100 parts by mass (b) Thermally conductive filler: 1,000 to 3,000 parts by mass (c) Silicone resin: 100 to 500 parts by mass (d) Organohydrogenpolysiloxane: 1 to 10 parts by mass (e) organic peroxide: 0.5 to 5 parts by mass, and (f) at least one selected from the following components (f-1) and (f-2): 1 to 20 parts by mass, (f-1) Alkoxysilane compound represented by the following general formula (1) R 2 a R 3 b Si(OR 4 ) 4-a-b (1) In the general formula (1), R 2 are independently an alkyl group having 6 to 15 carbon atoms, R 3 are independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 10 carbon atoms, R 4 are independently an alkyl group having 1 to 6 carbon atoms, a is an integer of 1 to 3, b is an integer of 0 to 2, wherein a+b is an integer of 1 to 3, (f-2) Dimethyl polysiloxane represented by the following general formula (2) In the general formula (2), R 5 Each of them is independently an alkyl group having 1 to 6 carbon atoms, and c is an integer of 5 to 100. 2 . The thermally conductive double-sided adhesive tape according to claim 1 , wherein the glass cloth is filled with the thermally conductive silicone composition.

3. The thermally conductive double-sided adhesive tape according to claim 1 or 2, wherein (c) the silicone resin comprises R3SiO 1 / 2 Unit and SiO 4 / 2 Unit, R3SiO 1 / 2 Unit and SiO 4 / 2 The molar ratio of the units is 0.1 to 3.0, and R represents an unsubstituted or substituted monovalent hydrocarbon group containing no aliphatic unsaturated bond. The thermally conductive double-sided adhesive tape according to claim 1 or 2, which has a thickness of 150 μm to 500 μm. 5 . The thermally conductive double-sided adhesive tape according to claim 1 , wherein (b) the thermally conductive filler is at least one selected from the group consisting of metals, metal oxides, and metal nitrides. 6 . The thermally conductive double-sided adhesive tape according to claim 1 , wherein a release-treated surface of a separator surface treated with a release agent is further laminated on the surface of the first adhesive layer or the second adhesive layer to which the glass cloth is not bonded. 7 . The thermally conductive double-sided adhesive tape according to claim 6 , wherein the release agent is a fluorine-modified silicone having a fluorine substituent bonded to the main chain. 8 . The thermally conductive double-sided adhesive tape according to claim 1 , which does not include a thermally conductive layer other than the first adhesive layer and the second adhesive layer.

9. A method for manufacturing a thermally conductive double-sided adhesive tape, comprising manufacturing the thermally conductive double-sided adhesive tape according to any one of claims 1 to 8, the method comprising: The step of laminating the first adhesive layer and the second adhesive layer on both sides of a glass cloth by room temperature compression bonding or thermal compression bonding to obtain the thermally conductive double-sided adhesive tape.

Citation Information

Patent Citations

  • Synthesis of 44**alkoxyy**methylcinnamic acidd4**cyanophenyl ester

    JP1977083346A

  • Heat dissipating pressure-sensitive adhesive composition and heat dissipating pressure-sensitive adhesive sheet using the same

    JP2002121529A

  • Thermally conductive tacky-adhesive tape

    JP2014034652A

  • Heat-conductive adhesive sheet and electronic / electric apparatus

    JP2014062220A